Measurement of W polarisation at LEP - Dova, María Teresa (2003)
The three different helicity states of W bosons produced in the reaction e+e− → W+W− → νqq ̄ at LEP are studied using leptonic and hadronic W decays. Data at centre-of-mass energies √s = 183–209 GeV are used to measure the polarisation of W bosons, and its dependence on the W boson production angle. The fraction of longitudinally polarised W bosons is measured to be 0.218 ± 0.027 ± 0.016 where the first uncertainty is statistical and the second systematic, in agreement with the Standard Model expectation.